Designing and Developing an Online Services System: A Case of Maybank Students' Residential Hall - Al Azawei, Ahmed H. Said (2009)
When internet services became cheap and available in the world, many organizations use it to enhance its benefits and to communicate with users in anywhere and anytime. Because that most universities used the facilities in online services to increase their abilities in organizing work. Online services are not limited to use in the universities for e-learning only. Although, the students who interact with online services increasingly, a common problem is that students online services need more efficient interaction. In other words, the sites lack usability; this research to design and develop an online services system for Maybank Students’ Residential Hall aid to solve this problem and to support the communication between students and residential hall staff.